Forward secure certificateless proxy multi-signature scheme. (3rd November 2020) - Gao, Ronghai; Zeng, Jiwen
In order to deal with key exposure problem, we introduce forward secure technique into certificateless proxy multi-signature scheme, and give the formal definition and security model of forward secure certificateless proxy multi-signature. Furthermore, we present a construction of forward secure certificateless proxy multi-signature scheme. Based on the difficulty of computational Diffie-Hellman problem, the proposed scheme is existentially unforgeable against adaptively chosen-message attacks and chosen-warrant attacks in the random oracle model. The proposed scheme does not use bilinear pairs in the key update and generation proxy signature phases, and updated proxy key is easy, thus it is more suitable for mobile environments. Our scheme has effectively dealt with the key exposure problem and certificate management problem.